Fatores ambientais que influenciam na ocupação de aves da Caatinga do Seridó - um estudo de caso na RPPN Stoessel de Brito - Almeida, Júlio Cezar Calderon de (2018)
Birds are one of the zoological groups that most suffer from the fragmentation of habitats caused by anthropic action. The Brazilian avifauna is composed of approximately 1,919 species, of which 510 of these species occur in the Caatinga. The birds deserve special attention because of their taxonomic diversity, characteristic of bioindicators and great capacity to move to choose their habitat, being that the evaluation of their community is an important tool to verify the degree of conservation and quality of the habitats. In view of this, we carried out an ornithological survey of the area with the purpose of enabling the characterization of the predominant birds in the environment. In this sense, the present study aimed to investigate how the environmental aspects and the intra and interspecific relations affected the distribution of groups of birds of the understory of the Seridó caatinga and estimate their occupation in their habitat. In this way we collected point-of-listening data in 40 sampling units during the period of lower rainfall. The study was done in the Private Natural Heritage Reserve (RPPN) Salobro Farm known as Stoessel de Britto, located in the municipality of Jucurutu, in the state of Rio Grande do Norte. The RPPN Stoessel de Brito contains a set of species of birds adapted to the Caatinga domain, which was classified according to the food habit, being considered the following trophic guilds: carnivorous, frugivorous, granivore, soil granivore, insectivorous, insectivorous soil, insectivorous trunk, nectarivore and omnivore. We use the MARK program to generate static occupation models, which incorporate the stochastic occupation and detection processes. The probability of occupation (Ψ) is defined as the proportion of habitat occupied by a species and the detection (p) is the probability of the target species being detected in a given area. We used occupation models for a species and a season. Thus, we obtained a set of models formed from the initial hypothesis where the environmental covariates influenced the detection and occupation of the guild of birds. In view of the analysis pointed out by the MARK program we had a very heterogeneous distribution of birds. It was observed that the trophic guilds of carnivores, frugivores, granivores, soil and insectivorous granivores, with the highest number of occupation points, standing out the granivores and insectivorous generalists with 92.5%, and soil granivores occupying 97, 5% of the sampling points, while the insectivorous trophic guilds of soil and insectivorous trunk presented 22.5% of their occupation, with their occupation influenced by environmental covariates.